SETS Learning Model in Biology: Strengthening Students’ Affective Competencies - Muhammad Nuruzzaman Shidiqi; Tesfaye Sahile (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This study aimed to analyze students’ affective learning outcomes through the implementation of the Science, Environment, Technology, and Society (SETS) learning model on fungi concepts in biology learning. The research specifically focused on students’ attitudes, learning interests, responsibility, discipline, cooperation, and environmental awareness during instructional activities. Methodology: This study employed a descriptive research design involving 65 tenth-grade students at Pasawahan State Senior High School 1. Data were collected using questionnaires, observation sheets, practical worksheets, and laboratory reports. The SETS learning model integrated laboratory practices, group discussions, and fermentation projects. Instrument validation was conducted through expert judgment, while data analysis used descriptive percentage techniques. Main Findings: The findings showed that the implementation of the SETS learning model improved students’ affective learning outcomes with an overall average score of 81.5%, categorized as very good. Practicum process assessment achieved the highest score of 82.2%, followed by laboratory reports at 81.0% and practical worksheets at 80.8%. Students demonstrated positive attitudes, responsibility, discipline, cooperation, learning enthusiasm, and environmental awareness during biology learning activities. Novelty/Originality of this study: The novelty of this study lies in its comprehensive analysis of affective learning outcomes through the SETS learning model on fungi concepts. Unlike previous studies emphasizing cognitive achievement, this research specifically examined discipline, responsibility, curiosity, cooperation, learning interest, and scientific attitudes through contextual laboratory activities, group discussions, worksheets, and fermentation projects integrated with environmental and societal applications.